PEMBUATAN PUPUK CAIR DAN BIOGAS DARI CAMPURAN LIMBAH SAYURAN - Erickson Sarjono Siboro; Edu Surya; Netti Herlina (Talenta Publisher (Universitas Sumatera Utara), 2013)
Garbage market activity results, which are not well experienced management will cause environmental pollution. The waste of vegetables still contains a high water content and contain organic ingredients, such as carbohydrates, proteins, and fats that one of them is a waste of vegetables. One method to manage waste of vegetables is to chop waste of vegetables with use the blender and mix with EM4 then fermented for 25 days. So it becomes an organic liquid fertilizer, because more quickly absorbed into the soil and quickly be used directly by plants, and can't damage the soil and plants. Preliminary data obtained from this study of the water content of 88.78%, pH 7.68, and the ratio of C / N 33.56. Final data with optimal results obtained on day 25 with the composition of the EM4 350 ml of N 1%, P 1.98%, K 0.85% and the ratio of C / N 30, total solid 34.78%, Chemical Oxygen Demand (COD) 2386 mg / L, pH 5.55 and 13 ml of biogas.